Properties of SiGe/Si heterostructures fabricated by ion implantation technique - Gomeniuk, Y.V.; Lysenko, V.S.; Osiyuk, I.N.; Tyagulski, I.P.; Valakh, M.Ya.; Yukhimchuk, V.A.; Willander, M.; Patel, C.J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
A comprehensive electrical characterisation of the SiGe/Si heterostructures has been performed in the wide temperature range (10270 K). Four structures fabricated by the Ge⁺ ion implantation technique at different substrate temperatures (room temperature, 150°C, 450°C and 600°C) have been studied. The diode I-V characteristics, thermally stimulated capacitance and currents were measured and the presence and parameters of shallow trap levels were determined in dependence on the substrate temperature. The sample implanted at 450°C shows the best diode operation reflecting the higher quality of the surface silicon layer as compared to RT- and 150°C-implanted samples. Implantation-induced mechanical stresses have been investigated by Raman spectroscopy. For the first time the cryogenic TSCR technique has been applied to this system which makes it possible to investigate strain in the silicon layer due to SiGe layer formation.